Origins of terrorism : psychologies, ideologies, theologies, states of mind - Reich, Walter, 1943- (Washington, DC : Woodrow Wilson Center Press, 1990)
Offers a study of the beliefs, goals, and other factors that cause groups and individuals to resort to violence to gain their political objectives.
Includes bibliographical references and index.
Keywords: Terrorism -- Psychological aspects; Terrorists -- Psychology